Post a New Question

algebra

posted by on .

2/w+ 4/w-1 = 10/w(w-1)

2(w-1)/w(w-1) + 4w/w(w-1)=10/w(w-1)
2w-2/w(w-1 +/4w/w(w-1= 10(w-1)/w(w-1)
2w-2+4w=10w-10
2w+4w-10w=-10-2
6w-10w=-10-2
-4w=8
w=2

  • algebra - ,

    w=2 satisfies the original equation, so I guess your solution is correct.

    However, the steps should be

    2(w-1)/2(w-1) + 4w/w(w-1) = 10/w(w-1)
    2w-2 + 4w = 10
    6w = 12
    w = 2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question